Effect of Fiber Type and Length on Strength, Fracture Energy, and Durability Properties of Microwave-Cured Fiber-Reinforced Geopolymer Mortars - Adil Gultekin (Buildings)
Microwave curing can be an alternative curing method for geopolymer production. Although many properties of microwave-cured geopolymer composites have been investigated, the effect of microwave curing on the strength and durability properties of fiber-reinforced geopolymers remains a topic that requires investigation. In this study, the effect of fiber type and length on the properties of microwave-cured metakaolin-based geopolymers was investigated. For this purpose, PVA (6, 12 mm) and polymer (15, 30 mm) fibers were utilized. Compressive and flexural strength, fracture energy, abrasion resistance, high-temperature resistance, water absorption capacity and rate of capillary water absorption tests were conducted and the microstructure was examined using scanning electron microscopy. For curing, a household microwave oven was used at a power level of 300 watts. With the fibers’ inclusion, fracture energies could be increased by up to 1150%, ductility was enhanced, flexural strengths were increased and compressive strengths decreased. Moreover, the rate of capillary water absorption decreased by up to 13%, while water absorption values increased by between 5% and 12%. The results suggested that microwave curing could be an alternative curing method for the production of fiber-reinforced geopolymer composites, offering shorter curing times and lower energy consumption.